PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE LEARNING START WITH A QUESTION UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN - Annisa Fitri; Hannisa Haris; Putri Hana Pebriana; Nurhaswinda; Fadhilaturrahmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve students' reading comprehension skills through the cooperative learning model type Learning Start with a Question (LSQ) in Grade V students at UPT SD Negeri 012 Kampung Panjang in the 2024/2025 academic year. The research used is Classroom Action Research (CAR). The subjects of this study are the students of UPT SD Negeri 012 Kampung Panjang, while the objects of the study are the cooperative learning model type Learning Start with a Question (LSQ) and the students' reading comprehension skills. The research was conducted in two Iteration, each consisting of two meetings. The data collection techniques used in this study were observation, tests, and documentation. Based on the increase in the number of students who achieved the minimum learning mastery criteria (KKTP) and the improvement in the average class scores and classical completeness, the results showed that the average scores and classical completeness in iteration I Meeting 1 were 31.25%, iteration I Meeting 2 was 50%, iteration II Meeting 1 was 75%, and iteration II Meeting 2 reached 87.5%. Based on these findings, it could be concluded that the cooperative learning model type Learning Start with a Question (LSQ) could improve the reading comprehension skills of Grade V students at UPT SD Negeri 012 Kampung Panjang.